Evaluations Of Probiotic Bacteria (Bacillus Spp.) As Dietary Additives On Growth Performance And Survival Rate Of Siamese Fighting Fish (Betta Splendens) - Sharifinia, Moslem; Haghparast, Mohammad Mahdi (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Effects of dietary administration of Bacillus subtilis, B. pumilus and B. licheniformis on growth performance and survival rate of Siamese fighting fish (Betta splendens). were evaluated in the present study. The experiment was conducted for 8 weeks with 12 h light: 12 h dark cycles and performed in triplicate with 10 dietary groups (one control and nine modified diets) comprised of 45 fish in each group. The treatments consisted of three levels at an initial concentration of 1× 106 CFU.g”1 (T1), 1× 107 CFU.g”1 (T2) and 1× 108 CFU.g”1 (T3) and one control, and were conducted every day. Siamese fighting fish (weight 0.1 ± 0.01 g) was fed with these diets and various growth indices and survival rate study were conducted for 8 weeks post-feeding. Survival percentage and condition factor of the diet containing 1 × 108 CFU.g”1 of B. subtilis had the best performance and showed a significant difference from other treatments (P< 0.05). The results suggest that Bacillus subtilis supplemented at a dose rate of 1 × 108 CFU.g”1 could significantly increase survival rate and is beneficial to Betta splendens.
Keywords: Diet; Duncan’s test; Growth index; Fish growth rate; Siamese fighting fish (Betta splendens)